Tata Kelola Keamanan Informasi dan Kepatuhan Etika melalui Prosedur Audit Trail - Muhammad Rajif Raditya; Evy Nurmiati (CV. ITTC INDONESIA, 2026)
The transformation of the Electronic-Based Government System (EBGS) faces critical challenges in the form of escalating insider threats that exploit governance loopholes. This study aims to evaluate the effectiveness of audit trails in detecting security anomalies, quantify IT professional ethics compliance, and test the reliability of audit trails as an objective validation instrument in the Indeks KAMI 5.0 assessment. The method used is a quantitative approach with a pre-experimental design utilizing a One-Group Pretest-Posttest model. Observations were conducted for 180 days on the XYZ Agency's infrastructure involving 45 IT personnel, utilizing Write-Once-Read-Many (WORM) encrypted Security Information and Event Management (SIEM) tools. The main results of this study redefine the functionality of log files from a mere reactive forensic instrument into a proxy metric for professional ethical compliance (based on the ACM and IEEE Codes of Ethics). The novelty of this research lies in the formulation of the Ethics and Security Compliance Index (IKEK), a mathematical model that deterministically converts database interaction anomalies into indicators of ethical violations and governance weaknesses.